Report of 27 lichenicolous fungi species and three genera new to Finland - Puolasmaa, Arto; Kuusisto, Inka (Finnish Mycological Society, 2025)
We studied systematically herbaria lichen specimens collected from Finland and from former Finnish parts of Russia to detect lichenicolous fungi. In total, 3355 lichen specimens were found with lichenicolous fungi from 160 taxa. We report here 27 species and three genera that are new to Finland. T hree of these, Cercidospora epithamnolia, Cyclothyrium sp. and Roselliniella stereocaulorum, are reported as also new to Scandinavia. Three taxa are reported from a new host.